Marketing Ideas: How to Write Research Articles that Readers Understand and Cite. (September 2021) - Warren, Nooshin L.; Farmer, Matthew; Gu, Tianyu; Warren, Caleb
Academia is a marketplace of ideas. Just as firms market their products with packaging and advertising, scholars market their ideas with writing. Even the best ideas will make an impact only if others understand and build on them. Why, then, is academic writing often difficult to understand? In two experiments and a text analysis of 1, 640 articles in premier marketing journals, this research shows that scholars write unclearly in part because they forget that they know more about their research than readers, a phenomenon called "the curse of knowledge." Knowledge, or familiarity with one's own research, exacerbates three practices that make academic writing difficult to understand: abstraction, technical language, and passive writing. When marketing scholars know more about a research project, they use more abstract, technical, and passive writing to describe it. Articles with more abstract, technical, and passive writing are harder for readers to understand and are less likely to be cited. The authors call for scholars to overcome the curse of knowledge and provide two tools—a website (writingclaritycalculator.com ) and a tutorial—to help them recognize and repair unclear writing so they can write articles that are more likely to make an impact.